The legal nature of timeshare - Rojas Ulloa, Milushka (2011)
Timeshare as a novel practice of acquiring real estate, is an institution through which the prerogative of using and enjoying exclusively and for a certain period of time, a furnished accommodation with its respective complementary services, that is, facilities is determined. sports facilities, swimming pools, gyms, computer entertainment rooms, and everything that allows the family to recreate in a healthy and healthy way. However, we know that not all of us have the necessary means to cover these costs, or if having this possibility, it is onerous to acquire a property to use it only for certain periods of the year, leaving most of the time unoccupied and carrying expenses at all times. maintenance and upkeep. For this reason, the importance of this system is reinforced by the fact that it is not only aimed at minorities with greater economic resources, but above all, this legal figure has been created with all social classes in mind, due to its affordable acquisition costs, allowing those interested in their moments of free disposition, to access vacation tourism through timeshare.